The Novel Fault Analysis Method of the Power Grid with Inverter Interfaced Distribution Generators - Yang, Zengli; Wang, Youhuai; Zhoug, Hubing; Wang, Linjun; Kong, Xiangping; Zhang, Zhe; Yin, Xianggen; Xiao, Fan (Distributed Generation & Alternative Energy Journal, 2016)
The special fault current characteristics of inverter interfaced dis - tribution generator (IIDG) make the conventional fault analysis method based on synchronous generator not applicable to a power grid with such IIDGs. In order to address this issue, according to the special fault current characteristics of IIDG, the problems of conventional fault analysis method when it is applied for the power grid with IIDGs are pointed out firstly. Based on it, a novel fault analysis method of the power grid with IIDGs is proposed. Lots of simulation cases show that the proposed fault analysis method has high calculation accuracy, which can meet the requirements of short-circuit calculation of the power grid and setting calculation of relay protection.